KEBIJAKAN PEMBANGUNAN DALAM PENGENTASAN KEMISKINAN MASYARAKAT PESISIR (Studi Kasus pada Masyarakat Pesisir di Kabupaten Purworejo, Jawa Tengah) - Arta Kusumaningrum (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2013)
Community development is a strategy to improve potencies of community and to be empowered. Poverty reduction should be done through community development program. Practices of community development is not only involve government, and pertinent institution as subject in poverty reduction but also involving society. Study case on coastal community in Purworejo Regency, with regard to community development policy has been directed to solve poverty in coastal community by analysing the cause of poverty, identify problem, and problem solving. Policy that can be taken is the idea to direct in creating program so that will be effective in poverty reduction for coastal community in Purworejo Regency. By involvement of many parties such as government, pertinent institutions, and society, the sustainability of poverty reduction program with community development as basic strategy can be sustain.